2018
DOI: 10.17559/tv-20160406110412
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Accuracy of VRS and Static GPS Measurement Results for Production of Topographic Map and Spatial Data: A Case Study on CORS-TR

Abstract: Abstract:The on-going developments in Global Navigation Satellite Systems (GNSS) technology affect techniques in geographic information and associated documents. The national Continuously Operating Reference Station (CORS) networks, which operate on the Real Time Kinematic (RTK) principle, are multi-purpose geodetic networks and offer services to a large portion of society including all the public institutions and other organizations, military and civilian users and to scientific researchers. It is possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Using the CORS-TR system, coordinate values can be generated with an accuracy of ±4 cm using a single fixed GNSS receiver within seconds, thanks to the network-RTK method [26]. In a previous CORS-TR-based study, according to [27], the maximum difference between static observation and measurements performed using the VRS method was obtained as −0.041 m in Easting, +0.048 m in Northing, and 0.088 m ellipsoid up value. Standard deviation for Easting, Northing, and ellipsoid up values were 0.019, 0.023, and 0.023 m, respectively.…”
Section: Cors-trmentioning
confidence: 99%
“…Using the CORS-TR system, coordinate values can be generated with an accuracy of ±4 cm using a single fixed GNSS receiver within seconds, thanks to the network-RTK method [26]. In a previous CORS-TR-based study, according to [27], the maximum difference between static observation and measurements performed using the VRS method was obtained as −0.041 m in Easting, +0.048 m in Northing, and 0.088 m ellipsoid up value. Standard deviation for Easting, Northing, and ellipsoid up values were 0.019, 0.023, and 0.023 m, respectively.…”
Section: Cors-trmentioning
confidence: 99%
“…Various surveying and mapping tasks, including establishing control points for aerial 1240 (2023) 012005 IOP Publishing doi:10.1088/1755-1315/1240/1/012005 2 photography, fixing boundary marks for cadastral survey, and monitoring real-time deformation for a geodetic survey. [1] The range of prices from low-cost systems with positioning accuracy of tens of meters to high-cost geodetic survey systems capable of positioning to the sub-centimetre level. Various methods can be applied using this GNSS tool.…”
Section: Introductionmentioning
confidence: 99%
“…The use of GNSS CORS network, also, allows applying differential corrections more reliable on wide areas, such as the Virtual Reference Station (VRS) approach [6], the Multi Reference Station (MRS) approach [7], the Flächen Korrektur Parameter (FKP) approach or other surface correction approaches [8,9]. Several authors [10][11][12] demonstrated that the NRTK technique allows reaching centimeter accuracy, comparable with the accuracy of the static measurements.…”
Section: Introductionmentioning
confidence: 99%